Business research for decision making - Davis, Duane; Cosenza, Robert M. (PWS-Kent Publishing Company, 1996)
The book is relevant to present and future managers who must use information obtained fromthe research process for decision-making purposes. In view of this focus, the fundamentals and techniques of research are presented in a highly readable fashion and are illustrated with many practical examples.